Analysis of factors influencing health-related quality of life in patients with femoropopliteal atherosclerotic occlusive disease treated with drug-coated balloons 12 months after surgery - Zhang, Yan; Lu, Shuangshuang; Fan, Weijian; Ye, Meng; Wu, Ziheng; Feng, Zibo; Guo, Lianrui; Shi, Zhenyu; Fang, Xin; He, Chunshui; Shi, Weihao; Cao, Yanpei (Frontiers in Surgery, 2025)
BackgroundPatients with femoropopliteal (FP) occlusive disease encounter considerable obstacles concerning health-related quality of life (HRQoL), which serve as the primary objectives of their interventions. While Drug-Coated Balloons (DCBs) present potential advantages, they are not constitute definitive cures. There is a paucity of research concerning postoperative HRQoL in these patients. This study evaluates HRQoL 12 months post-DCB treatment and examines influencing risk factors through a multicenter cross-sectional study.MethodsThis retrospective, multicenter study involved 1012 patients with FP occlusive disease who underwent DCB at 8 vascular centers from August 2021 to December 2023. Data on initial hospitalizations and 12-month follow-up were gathered, and logistic regression was utilized to examine the influencing factors.ResultsAccording to the median HRQoL at 12 months postoperatively, patients were categorized into low (N = 503) and high (N = 509) HRQoL groups. Significant differences were found in several variables such as renal insufficiency, calcification degree and TLR incidence (P < 0.05), while intervention approach (P = 0.781), DCB diameter (P = 0.301) and DCB length (P = 0.368) showed no significant differences. Logistic regression demonstrated that arterial calcification (OR = 0.33–0.44, P < 0.001), postoperative Rutherford classification (grade 1–6, OR = 0.0000 to 0.0367, P < 0.001), the Rutherford classification progression within 12 months (OR = 9.53, P < 0.001), and target lesion revascularization (TLR) occurrence (OR = 0.09, P = 0.011) were significantly linked to HRQoL at 12 months postoperatively, with no significant differences for other factors.ConclusionsOverall, the Rutherford classification progression over 12 months was significantly positively linked to HRQoL 12 months postoperatively. Conversely, HRQoL was notably diminished in patients who exhibited arterial calcification, elevated postoperative Rutherford classification, and experienced TLR. Nevertheless, intervention approach, DCB length and diameter had no significant relationship to postoperative HRQoL.